Principles of virology - Racaniello, Vincent (Henry Stewart Talks, 2020)
Introduction to virology, The ubiquity of viruses, The history of viruses and their discovery, Definition of a virus, Interactions between viruses and humans, Virus cultivation and the infectious cycle, The seven classes of viral genomes, The Baltimore scheme, Genetic manipulation of viruses